Stroke aftercare in Germany: findings from an online survey in the outpatient setting of a neurovascular network - Lee, John-Ih; Jansen, Robin; Cornelius, Jan F.; Schelzig, Hubert; Turowski, Bernd; Seitz, Rüdiger J.; Menge, Til; Albrecht, Philipp; Jander, Sebastian; Sobesky, Jan; von Giesen, Hans-Jürgen; Dihné, Marcel; et al. (Frontiers in Neurology, 2025)
The evidence-based acute treatment of stroke patients in Germany is carried out according to standardized algorithms in more than 300 certified stroke units, and its quality is repeatedly assured by the German Stroke Society (DSG) and others. However, nationally structured and uniform stroke aftercare programs are missing, despite evidence that they contribute to the success of rehabilitation and improvement of everyday life. We used a 27-item online questionnaire, which was mailed to 4,195 outpatient physicians in the catchment area of the neurovascular network Neurovascular Network North Rhine plus (NEVANO+) located in the western part of Germany to assess actual structures of stroke aftercare, identify barriers, and possible solutions. Based on 152 completed anonymous answers to the questionnaire, a descriptive evaluation revealed that general practitioners and neurologists are seen to be responsible for stroke aftercare. Important improvement aspects, among others, were identified in intersectoral cooperation, the use of a post-stroke checklist, and connections to local self-help organizations. Stroke units could play a key role in stroke aftercare by providing these checklists, connecting self-help organizations, and offering education and coaching for supportive coordinating staff. Furthermore, existing neurovascular networks can be expanded to include rehabilitation clinics, geriatric clinics, and outpatient physicians to improve intersectoral communication, collaboration, and post-stroke care. Further studies should investigate whether intersectoral cooperation, checklists, and cooperation with self-help organizations within an extended neurovascular network have a positive impact on stroke aftercare and patients’ quality of life.